1991
DOI: 10.1128/jvi.65.10.5440-5447.1991
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence and expression of the capsid protein gene of feline calicivirus

Abstract: The sequence of the 3'-terminal 2,486 bases of the feline calicivirus (FCV) genome was determined. This region of the FCV genome, from which the 2.4-kb subgenomic RNA is derived, contained two open reading frames. The larger open reading frame, found in the 5' end of the subgenomic mRNA, contained 2,004 bases encoding a polypeptide of 73,467 Da. The smaller open reading frame, encoded in the 3' end of the mRNA, was composed of 318 bases, encoding a polypeptide of 12,185 Da. The AUG initiation codon of the seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(51 citation statements)
references
References 31 publications
1
49
0
1
Order By: Relevance
“…Following this a small (58n) non-coding region extends to the poly-A tail a, the 3' terminus of the virus RNA. This structure is consistent with that of a calicivirus and is present in all feline calicivirus (FCV) strains sequenced, and is highly conserved [14][15][16].…”
Section: Cloning and Sequencing Proceduressupporting
confidence: 71%
See 1 more Smart Citation
“…Following this a small (58n) non-coding region extends to the poly-A tail a, the 3' terminus of the virus RNA. This structure is consistent with that of a calicivirus and is present in all feline calicivirus (FCV) strains sequenced, and is highly conserved [14][15][16].…”
Section: Cloning and Sequencing Proceduressupporting
confidence: 71%
“…It is unlikely therefore that this open reading frame directs a major antigen of the virus (Milton, unpublished observations). Neiii et al [16] suggest that this ORF may be translated as a fusion protein, joined to the major capsid gene product, by ribosome frameshifting. They suggest the sequence AUUAUGA, located at the gene junction, eoulcl direct this event [16].…”
Section: Discussionmentioning
confidence: 99%
“…A few other reported dicistronic mRNAs await testing. Wold et al, 1995;Ziff, 1985 Parvovirus: adeno-associated Capsid protein A Capsid proteins B/C Splicing Muralidhar et al, 1994 Hepatitis B virus Core protein S proteins (envelope) Promoter switch Schaller and Fischer, 1991 Retrovirus: avian, murine Gag (capsid) protein Env protein Splicing e Pawson et al, 1977;Van Zaane et al, 1977 Retrovirus: human foamy Gag (capsid) protein Pol precursor Splicing Jordan et al, 1996 Lentivirus: HIV-1 Tat Rev and Nef f Splicing Schwartz et al, 1992 Alphavirus: Semliki Forest Nonstructural proteins Capsid protein Internal promoter Glanville et al, 1976;Strauss and Strauss, 1994 Calicivirus: feline g Nonstructural proteins Capsid protein Independent replication Carter, 1990;Neill et al, 1991 a The silent downstream cistron identified in the third column is expressed only upon being moved closer to the 5 0 end via production of a second, shorter mRNA. Translation of most genes derived from these viruses follows straightforward predictions of the scanning mechanism, although occasional deviations have been reported.…”
Section: Silent Downstream Cistronsmentioning
confidence: 99%
“…All 24 mutants contained one or two point mutations within the major capsid protein (Table 3), giving a total of 20 unique mutations. Three of these mutations were present in the leader sequence of the capsid, which is cleaved from the capsid precursor protein during capsid assembly by a virusencoded proteinase (4,33,54); however, the mutants that contained mutations in the leader sequence also had an additional mutation in another region of the capsid protein. Several residue changes were found in more than one mutant.…”
Section: Selection Of Soluble Receptor-resistant (Srr) Mutants Of Fcvmentioning
confidence: 99%